(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
A retrospective investigation into the causes of mortalities of calves in dairy bovine breeding was carried out during the period going from 1992 to 2004 on the level of the farm pilot of Zérizer. A certain number of factors of risk were also considered: the age, the sex, the effect season, the effect bull and the effect pair. It was recorded during this period a death rate of 24,15% The principal causes of mortality are of a digestive nature with 45% against 25% for the respiratory problems. The summer is the season or mortality is most significant (38%). The most likely age is located between the birth and a week with a death rate reaching 34,72%. In addition, if one considers the age group lain between the birth and 3 months, the male death rate reached 69,44%, is more touched that males. We have noted mortalities in relation on the one hand, with certain bulls and on the other hand with certain pair.